State-building and national militaries in postcolonial West Africa decolonizing the means of coercion 1958-1974. - TURTIO, RIINA (Western Africa series, 2023)
Examines the role of the military in the decolonization and state-building process in francophone West Africa from 1958 to 1974. The book argues that the military played a fundamental role in this process, and that its influence can still be felt today.